Fecal microbiome and bile acid metabolome in adult short bowel syndrome - Boutte, Harold J.; Chen, Jacqueline; Wylie, Todd N.; Wylie, Kristine M.; Xie, Yan; Geisman, Mackenzie; Prabu, Anirudh; Gazit, Vered; Tarr, Phillip I.; Levin, Marc S.; Warner, Brad W.; Davidson, Nicholas O.; et al. (American journal of physiology: Gastrointestinal and liver physiology, 2022)
Loss of intestinal surface area causes short bowel syndrome, intestinal failure, and parenteral nutrition dependence. We analyzed the gut microbiota and bile acid metabolome of a large cohort of short bowel syndrome adult patients with different postsurgical anatomies. We report a novel analysis of the microbiome of patients with ileostomy and jejunostomy. Enrichment of specific microbial and bile acid species may be associated with the ability to wean from parenteral nutrition. Loss of functional small bowel surface area causes short bowel syndrome (SBS), intestinal failure, and parenteral nutrition (PN) dependence. The gut adaptive response following resection may be difficult to predict, and it may take up to 2 yr to determine which patients will wean from PN. Here, we examined features of gut microbiota and bile acid (BA) metabolism in determining adaptation and ability to wean from PN. Stool and sera were collected from healthy controls and from patients with SBS ( n = 52) with ileostomy, jejunostomy, ileocolonic, and jejunocolonic anastomoses fed with PN plus enteral nutrition or who were exclusively enterally fed. We undertook 16S rRNA gene sequencing, BA profiling, and 7α-hydroxy-4-cholesten-3-one (C4) quantitation with LC-MS/MS and serum amino acid analyses. Patients with SBS exhibited altered gut microbiota with reduced gut microbial diversity compared with healthy controls. We observed differences in the microbiomes of patients with SBS with ileostomy versus jejunostomy, jejunocolonic versus ileocolonic anastomoses, and PN dependence compared with those who weaned from PN. Stool and serum BA composition and C4 concentrations were also altered in patients with SBS, reflecting adaptive changes in enterohepatic BA cycling. Stools from patients who were weaned from PN were enriched in secondary BAs including deoxycholic acid and lithocholic aicd. Shifts in gut microbiota and BA metabolites may generate a favorable luminal environment in select patients with SBS, promoting the ability to wean from PN. Proadaptive microbial species and select BA may provide novel targets for patient-specific therapies for SBS. NEW & NOTEWORTHY Loss of intestinal surface area causes short bowel syndrome, intestinal failure, and parenteral nutrition dependence. We analyzed the gut microbiota and bile acid metabolome of a large cohort of short bowel syndrome adult patients with different postsurgical anatomies. We report a novel analysis of the microbiome of patients with ileostomy and jejunostomy. Enrichment of specific microbial and bile acid species may be associated with the ability to wean from parenteral nutrition.